De novo mutations of GCK, HNF1A and HNF4A may be more frequent in MODY than previously assumed - Stanik, Juraj; Dusatkova, Petra; Cinek, Ondrej; Valentinova, Lucia; Huckova, Miroslava; Skopkova, Martina; Dusatkova, Lenka; Stanikova, Daniela; Pura, Mikulas; Klimes, Iwar; Lebl, Jan; Gasperikova, Daniela; et al. (Diabetologia (Berlin), 2014)
AIMS/HYPOTHESIS: MODY is mainly characterised by an early onset of diabetes and a positive family history of diabetes with an autosomal dominant mode of inheritance. However, de novo mutations have been reported anecdotally. The aim of this study was to systematically revisit a large collection of MODY patients to determine the minimum prevalence of de novo mutations in the most prevalent MODY genes (i.e. GCK, HNF1A, HNF4A). METHODS: Analysis of 922 patients from two national MODY centres (Slovakia and the Czech Republic) identified 150 probands (16%) who came from pedigrees that did not fulfil the criterion of two generations with diabetes but did fulfil the remaining criteria. The GCK, HNF1A and HNF4A genes were analysed by direct sequencing. RESULTS: Mutations in GCK, HNF1A or HNF4A genes were detected in 58 of 150 individuals. Parents of 28 probands were unavailable for further analysis, and in 19 probands the mutation was inherited from an asymptomatic parent. In 11 probands the mutations arose de novo. CONCLUSIONS/INTERPRETATION: In our cohort of MODY patients from two national centres the de novo mutations in GCK, HNF1A and HNF4A were present in 7.3% of the 150 families without a history of diabetes and 1.2% of all of the referrals for MODY testing. This is the largest collection of de novo MODY mutations to date, and our findings indicate a much higher frequency of de novo mutations than previously assumed. Therefore, genetic testing of MODY could be considered for carefully selected individuals without a family history of diabetes.
Keywords: Czech Republic; Česká republika; Hepatocyte Nuclear Factor 1-alpha; Protein Serine-Threonine Kinases; protein-serin-threoninkinasy; genetická predispozice k nemoci; prevalence; Pedigree; rodokmen; Mutation; hepatocytární jaderný faktor 1-alfa; Humans; Genetic Testing; Germinal Center Kinases; Slovenská republika; sekvenční analýza DNA; Diabetes Mellitus, Type 2; kinázy zárodečného centra; diabetes mellitus 2. typu; hepatocytární jaderný faktor 4; Hepatocyte Nuclear Factor 4; Slovakia; Prevalence; Sequence Analysis, DNA; genetické testování; mutace; Genetic Predisposition to Disease; lidé